Weeding the nettles III: Named nonsense versus named morphotypes in European Urtica dioica L. (Urticaceae) - Grosse-Veldmann, Bernadette; Weigend, Maximilian (Phytotaxa, 2015)
Urtica dioica L. in its wider sense is reported from nearly all temperate zones of the world, from throughout Eurasia, from North America and South America, from S Africa and New Zealand. In Europe, over 70 infrasubspecific names referable to the widespread and often weedy U. dioica subsp. dioica have been used in one form or another; over 40 of them are formally described. Many of these names are invalid and/or superfluous. However, several identifiable morphotypes can be found, which are stable in cultivation and usually occur in several different regions of Europe and/or are characterized by some type of habitat preference. These morphotypes in their most characteristic expression are quite well differentiated, but are connected by a continuous series of intermediates in nature. As a working hypothesis we here propose the tentative recognition of the following five morphotypes: U. dioica subsp. dioica var. dioica, -var. hispida, -var. sarmatica, -var. holosericea, and -var. glabrata. A characterization of each morphotype and corresponding synonyms are presented here based on extensive field studies, literature and herbarium studies and cultivation of material. Lecto-and neotypes are designated where necessary for some of the more important names.